Effects of Length of Storage, Relative Humidity (RH) and Temperature On the Stability of lodized Salt - Wisnu Cahyadi (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2008)
Iodine deficiency disorders (IID) is still a major public health problem in several areas of the world. Especially in developing countries. The problem of iodine decrease or loss in iodized salt and food-stuff during processing is still the a controversial issue, among public, functionary, even the scientist. The stability of iodine is influenced by the food type, water content and cooking temperature. The objective of this research was to determine the effects of length of storage, relative humidity (RH) and temperature on the stability of iodized salt. Analysis of iodium was performed using Ion Pair High Perfomance Liquid Chromatography (HPCL). The rate of iodine decrease was influenced by salt origin, temperature, packaging material and RH during storage. The result of research showed that the percentage of iodate decrease in iodized salt packaged by high density polyethylene (HDPE) were 66.86% and 50.85% during storage for 14 days at temperature of 400C, RH 60% and 100%. Other result showed that the percentage of iodate decrease in iodized salt was 46.51% during storage for 28 days at temperature of 25.50C and RH 60-65%. Key words : Iodine Deficiency Disorders, stability of iodized salt, ion pair-HPLC